OPTIMIZING ENGLISH LANGUAGE LEARNING. EFFECTIVE STRATEGIES FOR ORGANIZING ENGAGING LESSONS - Hasanova Dilnoza Gayratovna (American Journals, 2025)
Organizing English lessons is a crucial aspect of effective language teaching, as it sets the foundation for engaging and impactful learning experiences. This article explores various strategies and best practices for organizing English lessons, including lesson planning, instructional design, classroom management techniques, and assessment strategies. By examining the key components of lesson organization and their impact on student learning outcomes, this article aims to provide educators with practical insights to enhance the quality and effectiveness of English language lessons.
Keywords: Effective lesson planning, educators, learning objectives, lesson content, different teaching methods